The Level of Participants Creativity in Learning Sewing Skills at the Korsa Sewing Course Institution Malang City - Anggraini, Sofiana Fitria; Redjeki, Endang Sri; Choiro, Umu Da’watul (Proceedings Series of Educational Studies, 2024)
The purpose of this research was to determine: The level of creativity of participants in taking part in learning sewing skills at the Korsa Course in Malang City. The results of the research show: 1) The level of creativity of participants in participating in fluency thinking fluency skills learning has an average of 3,24 and the percentage of this sub variable has 3 indicators, namely imagination, freedom in thinking, getting more than 1 idea, you can get a score from the whole namely 80,92% which is categorized as very high. 2) The level of creativity of the participants in terms of flexibility of thinking has an average score of 3,16 and the percentage of this sub variable has 2 indicators, namely point of view, and spontaneous thinking when seeing something. The overall score can be obtained, namely 78,31% which is categorized as very high. 3) Overall, the assessment of the level of creativity of participants in taking part in learning original thinking skills (originality) in creating unique ideas/scenes has an average score of 3,13 and the percentage score is 77,47% or the same as very high. (4) Overall, the assessment of the level of creativity of participants in participating in elaboration skills learning to describe and develop ideas has an average score of 3,18 and the percentage score is 79,46% or the same as very high.